Reduced Working Memory Mediates the Link between Early Institutional Rearing and Symptoms of ADHD at 12 Years - Tibu, Florin; Sheridan, Margaret A.; McLaughlin, Katie A.; Nelson, Charles A.; Fox, Nathan A.; Zeanah, Charles H. (Frontiers in Psychology, 2016)
Children who are raised in institutions show severe delays across multiple domains of development and high levels of psychopathology, including attention deficit/hyperactivity disorder (ADHD). Low performance in executive functions (EFs) are also common in institutionally-reared children and often do not remediate following improvements in the caregiving environment. ADHD symptomatology also remains elevated even after children are removed from institutional care and placed in families. We investigate whether poor EF is a mechanism explaining elevated rates of ADHD in children reared in institutional settings in the Bucharest Early Intervention Project (BEIP). In the current study we examine the potentially mediating role of poor EF in the association between institutionalization and symptoms of ADHD at age 12 years. A total of 107 children were assessed with the Cambridge Neuropsychological Test Automated Battery (CANTAB) on working memory, set-shifting and planning. We also obtained concurrent teacher reports on their levels of ADHD symptoms (inattention and impulsivity separately). Institutionalization strongly predicted elevations in symptoms of inattention and impulsivity at age 12 years (ps < .01). Indices of working memory and planning were also associated with ADHD after controlling for potential confounders (ps < .03). Mediation analyses revealed that poor working memory performance mediated the link between exposure to early institutionalization and higher scores of both inattention and impulsivity. These results replicate and extend the findings that we reported in the BEIP sample at age 8 years. Together, they suggest that compromised working memory is a key mechanism that continues to explain the strikingly high levels of ADHD in late childhood among children institutionalized in early life. Interventions targeting working memory may help to prevent ADHD among children exposed to institutional care.